Advancements in Antimicrobial Biomaterials: New Avenues to Ameliorate Wound Infections and Implant-associated Infections - Mukherjee, Sudip; Patra, Dipanjana; Maity, Subhankar; Haldar, Jayanta (Current Indian Science, 2025)
The field of public healthcare has witnessed a transformative shift with the introduction of synthetic biomaterials and biomedical implants, aiming to enhance the interaction between living systems and therapeutic interventions. Despite these advancements, a significant challenge has emerged in the form of microbial colonization and biofilm formation on these materials, leading to an alarming rise in multidrug-resistant infections and subsequent implant rejections. In this review, we present recent breakthroughs in the development of anti-infective biomaterials designed to address wound infections and prevent infections associated with implants. We present various approaches for incorporating antimicrobial properties into diverse wound healing biomaterials such as hydrogels and hemostatic sponges, through covalent and non-covalent modifications or both. Additionally, to counter microbial colonization, we explore different surface modification strategies applied to titanium and catheter implants via covalent grafting as well as physical encapsulation of antibiotics, small molecular biocides, inorganic biocides and antimicrobial peptides. These coatings not only exhibit bacteria-killing capabilities upon contact but also effectively reduce biofilm formation, thereby prolonging the lifespan of implants and devices. Providing an overview of anti-infective biomaterials in clinical pipelines, we discuss the significant challenges hindering the clinical translation of these biomaterials. Finally, we share our perspective on overcoming these obstacles for the successful integration of anti-infective biomaterials into mainstream healthcare practices.
Keywords: Antimicrobial biomaterials